Características sociodemográficas y depresión posparto en madres de neonatos en cuidados intensivos Perú - Haro-Norabuena, Rosana (2025)
Objective. To determine the sociodemographic characteristics associated with postpartum depression among mothers of neonates admitted to the intensive care unit of Hospital Nacional Guillermo Almenara Irigoyen, Lima (Peru), 2024. Methods. A quantitative, non-experimental, comparative, cross-sectional study was conducted. The census sample consisted of 180 mothers of neonates in intensive care. The Edinburgh Postnatal Depression Scale (EPDS) was used as the measurement instrument. For inferential analysis, chi-square and Kendall’s tau-b tests were applied. Results. Overall, 47.7 % of mothers were between 28 and 36 years old, 72.2 % were employed, 78.3 % were born in and resided in Lima, and 97.8 % reported having access to basic services. Postpartum depression was present in 60.6 % of the study population. There was a significant association between postpartum depression and age (p = 0.034) and place of residence (p = 0.001). Conclusions. Age and place of residence were the sociodemographic characteristics significantly associated with postpartum depression among mothers of neonates admitted to the intensive care unit of Hospital Nacional Guillermo Almenara Irigoyen.